Development of a Portable Spirometer with MPX5500DP Air Pressure Sensor and Atmega328 Microcontroller - Juliandri, Dona; Erliwati, Erliwati; Yudithia, Frenzi Agres; Febrian, Fikri (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2024)
This study presents the development of a groundbreaking portable spirometer designed to improve respiratory health monitoring by addressing the limitations of traditional, bulky spirometers that are confined to clinical settings. The device leverages the MPX5500DP air pressure sensor and the Atmega328 microcontroller to deliver accurate and sensitive measurements of air pressure changes, which are crucial for assessing lung volume and airflow. The integration of these components enables the spirometer to convert air pressure variations into electrical signals. These signals are processed by the microcontroller and displayed on an LCD screen, providing users with clear and precise lung function data. Rigorous testing and calibration of the spirometer have validated its performance, showing an overall accuracy of 94% for voltage measurements. Functional testing further confirms the device's precision, achieving an impressive 99.14% accuracy for inspiration capacity and 85.51% for expiration capacity. These results underscore the device’s reliability and effectiveness as a significant advancement in respiratory health technology. Its portable and user-friendly design makes it a practical tool for both personal health monitoring and clinical applications. By enhancing the accessibility and ease of respiratory assessments, this spirometer has the potential to improve everyday health management and clinical evaluations, thus representing a substantial leap forward in the field of respiratory health technology.